Methodology of accelerated weathering test through physicochemical analysis for polymeric materials in building construction. (May 2014) - Yang, T. C.; Wu, J. H.; Noguchi, T.; Isshiki, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Physicochemical analysis in the microscopic sense is a critical assessment of monitoring the polymeric materials under a weathering test, and it links the accelerated laboratory test with the outdoor performance results for a long-term durability. Here, by taking an experimented example for vinyl siding after an outdoor weathering test in Okinawa, Japan for 17 years and a QUV accelerated weathering test for 2880 hours, it was observed that there were entirely different results on the functional groups and the surface image with the atom concentration measured by the attenuated total reflectance Fourier transform infrared and scanning electron microscopy with energy dispersive spectroscopy, respectively. Furthermore, the optimal conditions of a specified accelerated weathering test based on a replication of the natural weathering characteristics are deliberated, thus correcting the deterioration factors configuration in consideration for the physicochemical degradation of a specific material. The aim of this study places an emphasis on the crucial points for improving the accelerated weathering test through a physicochemical analysis.